A Common Thrombomodulin Amino Acid Dimorphism Is Associated with Myocardial Infarction - Norlund, Lena; Holm, Johan; Zöller, Bengt; Öhlin, Ann-Kristin (Thrombosis and Haemostasis, 1997)
Endothelial dysfunction and haemostatic imbalance are believed to be important aetiological factors in the development of acute coronary syndromes. Thrombomodulin (TM) is an integral membrane protein crucial for normal endothelial function and activation of the protein C anticoagulant pathway. We have investigated the importance of a common C/T dimorphism in the TM gene (nucleotide 1418) for development of premature myocardial infarction (MI). The C/T dimorphism predicts an Ala455 to Val replacement in the sixth EGF-like domain of TM. The dimorphism was investigated in 97 MI survivors and 159 healthy controls. The C allele was significantly more frequent among patients than controls (p = 0.035). The allele frequency for the C allele was 0.82 in the patients and 0.72 in the control group. The plasma concentration of TM was investigated among healthy controls but was not related to the C/T dimorphism. In conclusion, the association of the C allele with premature MI, suggests that the TM gene and the C/T dimorphism may be aetiological factors involved in the pathogenesis of MI. Possibly, the Ala455 to Val replacement may affect the function of the TM molecule and the activation of the protein C anticoagulant pathway.